Optimal dietary practices and nutritional knowledge of school adolescent girls in Jimma Town, South West Ethiopia - Yabsira Melaku; Anteneh Dirar; Garumma Tolu Feyissa; Dessalegn Tamiru (International Journal of Adolescence and Youth, 2018)
Addressing the nutritional problems of adolescent girls is important as their nutritional status has a negative effect on the future generation. This study aimed to assess the optimal dietary practices and nutritional knowledge of school adolescent girls in Jimma Zone, South-west Ethiopia. School-based cross-sectional study was conducted among 455 school adolescent girls. Multivariable logistic regression was used to identify independent variables. Majority (61.3%) of students had dietary diversity score less than five and their mean (±SD) dietary diversity score was 4.34 ± 1.41. The majority (55.8%) of adolescent girls had a good knowledge score about nutrition related information which they earned from the school (86.6%). Low dietary diversity of school adolescent girls was positively associated with attending government schools, lack of maternal education and low-economic status. Therefore, both government and non-government organizations need to focus on school and community based nutrition intervention to address the low dietary diversity of school girl adolescents.